Association between platelet-lymphocyte ratio and 90-day mortality in patients with intracerebral hemorrhage: data from the MIMIC-III database - Yuan, Min; Xiao, Zhilong; Zhou, Huangyan; Fu, Anxia; Pei, Zhimin (Frontiers in Neurology, 2023)
Background Recent evidence suggested that platelet-lymphocyte ratio (PLR) may play a role in the pathophysiology of intracerebral hemorrhage (ICH), but the results are controversial. This study aimed to explore the relationship between PLR and mortality in patients with ICH. Methods All data were extracted from the Medical Information Mart for Intensive Care (MIMIC) III database. The study outcome was 90-day mortality. Multivariable Cox regression analyses were used to calculate the adjusted hazard ratio (HR) with a 95% confidence interval (CI), and curve-fitting (restricted cubic spline) was used to assess the non-linear relationship. Results Of 1,442 patients, 1,043 patients with ICH were included. The overall 90-day mortality was 29.8% (311/1,043). When PLR was assessed in quartiles, the risk of 90-day mortality for ICH was lowest for quartile 2 (120.9 to <189.8: adjusted HR, 0.67; 95% CI: 0.48–0.93; P = 0.016), compared with those in quartile 1 (<120.9). Consistently in the threshold analysis, for every 1 unit increase in PLR, there was a 0.6% decrease in the risk of 90-day mortality for ICH (adjusted HR, 0.994; 95% CI: 0.988–0.999) in those with PLR <145.54, and a 0.2% increase in 90-day mortality (adjusted HR, 1.002; 95% CI: 1.000–1.003) in participants with PLR ≥145.54. Conclusion There was a non-linear relationship between PLR and 90-day mortality for patients with ICH, with an inflection point at 145.54 and a minimal risk at 120.9 to <189.8 of PLR.